Elevated admission N-terminal pro-brain natriuretic peptide level predicts the development of atrial fibrillation in general surgical intensive care unit patients. Issue 3 (September 2017) - Chokengarmwong, Nalin; Yeh, Daniel Dante; Chang, Yuchiao; Ortiz, Luis Alfonso; Kaafarani, Haytham M.A.; Fagenholz, Peter; King, David R.; DeMoya, Marc; Butler, Kathryn; Lee, Jarone; Velmahos, George; Januzzi, James Louis; et al.
Abstract : BACKGROUND: New onset atrial fibrillation (AF) in critically ill surgical patients is associated with significant morbidity and increased mortality. N-terminal pro-B type natriuretic peptide (NT-proBNP) is released by cardiomyocytes in response to stress and may predict AF development after surgery. We hypothesized that elevated NT-proBNP level at surgical intensive care unit (ICU) admission predicts AF development in a general surgical and trauma population. METHODS: From July to October 2015, NT-proBNP concentrations were measured at ICU admission. Abnormal NT-proBNP concentrations were defined by age-adjusted cut-offs. We examined the relationship between the development of AF and demographics, clinical variables, and NT-proBNP level using univariate analysis and a multivariable logistic regression model. RESULTS: Three hundred eighty-seven subjects were included in the cohort, none of whom were in AF at ICU admission. The median age was 63 years (52–73 years), and 40.3% were women. The risk of developing AF was higher for abnormal versus normal NT-proBNP (22% vs. 4%; p < 0.0001). Using optimal derived cutoffs (regardless of age), the risk of developing AF was 2% for NT-proBNP less than 600 ng/L, 15% for NT-proBNP of 600 ng/L to 1, 999 ng/L, and 27% for NT-proBNP of 2, 000 ng/L or greater. Multiple logistic regression analysis identified three independent predictors for new-onset AF: age, older than 70 years (odds ratio [OR], 3.7, 95% confidence interval [CI], 1.5–9.3), history of AF (OR, 25.3; 95% CI, 9.6–67.0), and NT-proBNP of 600 or greater (OR, 4.3; 95% CI, 1.3–14.2). When none or only one predictor was present, AF incidence was less than 1%. When all three predictors were present, AF incidence was 66%. For subjects 70 years or older but no history of AF, AF incidence was 12.8% when NT-proBNP was 600 or greater compared with 0% when NT-proBNP was less than 600. For subjects younger than 70 years with a history of AF, AF incidence was 44.4% when NT-proBNP was 600 or higher compared to 0% when NT-proBNP was less than 600. CONCLUSION: Elevated NT-proBNP at ICU admission in general surgical and trauma patients is predictive of AF development in the first 3 ICU days. Addition of NT-proBNP measurement to known risk factors can improve predictive power and identify patients who might potentially benefit from evidence-based prophylactic treatment for AF.